Characterization and Antioxidant Activity of Phenolic Extracts from Oil Palm (Elaeis Guineensis) Fruits - Neo, Yun Ping (2009)
The extracted oil palm fruit phenolics were analysed using spectrophotometry methods to obtain information on the different types of oil palm phenolics and their antioxidative activities. Different methods were used to extract soluble free (SFP), insoluble-bound (ISBP) and esterified (EFP) phenolics for a better understanding of the types of phenolics present. TPC, TFC, ODPI and DPPH of oil palm phenolics were also monitored to investigate the possible relationships between these variables and the degree of maturity/ripeness of the oil palm fruit from 16 to 24 weeks. The antioxidant activities of oil palm phenolic extracts were analysed using different antioxidant assays, namely the 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assay, 2,2-diphenyl-2-picrylhydrazyl (DPPH) assay, the ferric-reducing ability (FRAP) assay, β-carotene bleaching assay (BCB) and the oxidative stability index (OSI). Results showed that oil palm phenolic extracts contained high antioxidant activities in the order of ISBP > EFP > SFP. Eight different phenolic acids were identified and quantified using a simple reversed-phase high performance liquid chromatography (HPLC) with a diode array detector (DAD) and liquid chromatography/ tandem mass spectrometry (LC/MS/MS). Gallic, protocatechuic, p-hydroxybenzoic, vanillic, caffeic, syringic, p-coumaric and ferulic acids were detected in oil palm phenolic extracts. Ferulic, p-hydroxybenzoic and p-coumaric acid were the dominant phenolic acids found in oil palm fruit extracts and ranged from 55 - 376 μg/g of DW. The results suggested the potent antioxidant activities of oil palm phenolic extracts and the presence of phenolic acids in palm fruits.